2006
DOI: 10.1111/j.1365-2427.2005.01499.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐substrate interactions create and mediate leaf litter resource patches in streams

Abstract: 1. The roles that streambed geometry, channel morphology, and water velocity play in the retention and subsequent breakdown of leaf litter in small streams were examined by conducting a series of field and laboratory experiments. 2. In the first experiment, conditioned red alder (Alnus rubra Bongard) leaves were released individually in three riffles and three pools in a second-order stream. The transport distance of each leaf was measured. Several channel and streambed variables were measured at each leaf set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 50 publications
(117 reference statements)
4
85
2
2
Order By: Relevance
“…In order to colonize leaves in riffles, the macroinvertebrates need adaptations that enable them to remain adhered to the substratum in conditions of strong flow (KOBAYASHI & KAGAYA 2002). HOOVER et al (2006) verified a higher rate of decomposition of litter in pools and suggested that litter in riffles may be accessible only for a limited group of detritivorous macroinvertebrates, a situation that could lead to a decrease in the rates of biological fragmentation in riffles. The smaller oxygenation rates in pools, however, may inhibit the colonization by taxa with high oxygen requirements (KOBAYASHI & KAGAYA 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In order to colonize leaves in riffles, the macroinvertebrates need adaptations that enable them to remain adhered to the substratum in conditions of strong flow (KOBAYASHI & KAGAYA 2002). HOOVER et al (2006) verified a higher rate of decomposition of litter in pools and suggested that litter in riffles may be accessible only for a limited group of detritivorous macroinvertebrates, a situation that could lead to a decrease in the rates of biological fragmentation in riffles. The smaller oxygenation rates in pools, however, may inhibit the colonization by taxa with high oxygen requirements (KOBAYASHI & KAGAYA 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Low organic matter standing stocks in the buried reaches likely resulted from a combination of reduced allochthonous and autochthonous inputs and limited retention. The buried reaches had greatly simplified geomorphology with few in-stream devices to physically retain organic matter for subsequent microbial processing (Hoover et al 2006).…”
Section: Effect Of Stream Burial On Nomentioning
confidence: 99%
“…Litter breakdown process is also influenced by hydrological regime, especially current velocity and high-flow events (Bird & Kaushik, 1992;Lepori et al, 2005;Paul et al, 2006). While stream flow alone plays a minor role in determining breakdown directly, its effect seems more usually indirect by way of an influence on biological processes (Woodcock & Huryn, 2005;Ferreira et al, 2006;Hoover et al, 2006). For instance, breakdown rates of two leaf species in an Arizona stream decreased by *20% when flows were reduced by 95%, and this decrease was associated with cooler temperatures as well as lower fungal biomass and macroinvertebrate diversity on the leaves (Muehlbauer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%